2016
DOI: 10.1016/j.actbio.2016.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Bio-identity and fate of albumin-coated SPIONs evaluated in cells and by the C. elegans model

Abstract: Unravelling meaningful relationships between the physiological impact of engineered nanoparticles and their synthetic and biological identity is of vital importance when considering nanoparticles biomedical uses and when establishing their nanotoxicological profile. This study contributes to better comprehend the inorganic nanoparticles' behavior in real biological milieus. We synthesized a controlled pre-formed BSA protein corona on SPIONs to lower unspecific cell uptake and decrease nanoparticle fouling with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 56 publications
1
33
0
Order By: Relevance
“…According to a survey, the N use rate by winter wheat and summer corn was only 28.2% and 26.1%, respectively. This rate is, however, much lower than that of the world's average, that is, 33.5% and 37% for wheat and corn, respectively (Zhang et al, 2008;Yu et al, 2016). N fertilizer is a key factor for obtaining high yields in the corn-wheat rotation system.…”
Section: Introductionmentioning
confidence: 90%
“…According to a survey, the N use rate by winter wheat and summer corn was only 28.2% and 26.1%, respectively. This rate is, however, much lower than that of the world's average, that is, 33.5% and 37% for wheat and corn, respectively (Zhang et al, 2008;Yu et al, 2016). N fertilizer is a key factor for obtaining high yields in the corn-wheat rotation system.…”
Section: Introductionmentioning
confidence: 90%
“…On the biomedical side, Gonzalez-Moragas et al reported lower toxicity of albumin-coated Fe 2 O 3 -NPs compared to citrate-stabilized Fe 2 O 3 -NPs, and attributed it to the reduced interaction of the former with the C. elegans cells, confirming the impact of a controlled surface coating on the bio-identity of NPs in vivo . [34, 67] …”
Section: Factors Influencing Nano/bio Interactions In C Elegansmentioning
confidence: 99%
“…However, SPIONs also triggered a response of intestinal-related genes which might indicate that the proximity of the luminal NPs to the microvilli can influence microvilar structure and its remodeling processes. Although SPIONs did not cause intestinal cytotoxicity or structural damage at 24 hours, (Yu et al, 2016a) we do not discard that a prolonged contact with NPs could lead to irreversible damage on the intestinal barrier. (Zhao et al, 2014) Ferritin up-regulation occurred after SPION and Au-NP treatment, and similar effects were observed after C. elegans exposure to arsenic, cadmium and ethosuximide.…”
Section: Evaluation Of Specific Molecular Markersmentioning
confidence: 99%
“…(Yu et al, 2016a). qPCR experiments showed that the pre-formed protein corona of the BSASPIONs mitigated the harmful effects compared to Cit-SPIONs, especially at low doses.…”
Section: Predicted Model Of Spion Toxicitymentioning
confidence: 99%
See 1 more Smart Citation